If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(x + 1) + ln(x + 4) = ln(x + 9) Reorder the terms: ln(1 + x) + ln(x + 4) = ln(x + 9) (1 * ln + x * ln) + ln(x + 4) = ln(x + 9) (1ln + lnx) + ln(x + 4) = ln(x + 9) Reorder the terms: 1ln + lnx + ln(4 + x) = ln(x + 9) 1ln + lnx + (4 * ln + x * ln) = ln(x + 9) 1ln + lnx + (4ln + lnx) = ln(x + 9) Reorder the terms: 1ln + 4ln + lnx + lnx = ln(x + 9) Combine like terms: 1ln + 4ln = 5ln 5ln + lnx + lnx = ln(x + 9) Combine like terms: lnx + lnx = 2lnx 5ln + 2lnx = ln(x + 9) Reorder the terms: 5ln + 2lnx = ln(9 + x) 5ln + 2lnx = (9 * ln + x * ln) 5ln + 2lnx = (9ln + lnx) Solving 5ln + 2lnx = 9ln + lnx Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-9ln' to each side of the equation. 5ln + -9ln + 2lnx = 9ln + -9ln + lnx Combine like terms: 5ln + -9ln = -4ln -4ln + 2lnx = 9ln + -9ln + lnx Combine like terms: 9ln + -9ln = 0 -4ln + 2lnx = 0 + lnx -4ln + 2lnx = lnx Add '-1lnx' to each side of the equation. -4ln + 2lnx + -1lnx = lnx + -1lnx Combine like terms: 2lnx + -1lnx = 1lnx -4ln + 1lnx = lnx + -1lnx Combine like terms: lnx + -1lnx = 0 -4ln + 1lnx = 0 Factor out the Greatest Common Factor (GCF), 'ln'. ln(-4 + x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-4 + x)' equal to zero and attempt to solve: Simplifying -4 + x = 0 Solving -4 + x = 0 Move all terms containing l to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + x = 0 + 4 x = 0 + 4 Combine like terms: 0 + 4 = 4 x = 4 Add '-1x' to each side of the equation. x + -1x = 4 + -1x Combine like terms: x + -1x = 0 0 = 4 + -1x Simplifying 0 = 4 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -2(5x+4)=-27x-18-7 | | 3x+6+x-11+x-10=360 | | 3.2d=15.75-54.15 | | 3x+4(x+6)=410 | | 6+7x=4x+18 | | 2x+27=6x+3 | | .5x+3y=2 | | .67=ln(y) | | h=16t^2+vt+s | | 12+(5-9)= | | 3.2d=15.75+54.15 | | 7-x=7x+39 | | 6x+2x-9=95 | | -5x-2=x-2 | | 20x+35x=121 | | 5-2(x+2)=13 | | 14x-3+30=16x+11 | | x/3*4=20 | | 95=8x-8 | | 5+2(3x-8)=2x+9 | | 11+d+(-4)ford=-6 | | k^2-32k+8=0 | | 3(8.2-x)=6.6 | | -2(3x-2)=4-6x | | 26=6(5-a)+2 | | 7*5=63-N | | x/34=20 | | 56=t-25 | | 12x+11+69=25x+2 | | -5x-4=-3x+10 | | -10p-8=2 | | 3x+10y=-4 |